Framework for a standard form of joint venture agreement for construction works - Abdul Rashid, Khairuddin; Samsuddin, Mohamad Shafiq Amin; Hasan, Sharina Farihah (2010)
The absence of a standard form of joint venture agreement for construction works has led parties intending to form a joint venture to resort to custom-made or in-house agreement often drafted by the parties themselves. Consequently, some joint venture agreements may have been established on ad-hoc and possibly incomplete basis and even entirely orally. In an effort ot address this and other issues arising from the absence of a standard of joint venture agreement a two-stage study was conducted. The first part of the study involved critical examination of joint venture agreements made available to the first author, and the second part of the study was carried out by way of a questionnaire survey among contractors currently involved or known to have been involved in joint ventures for construction works. The study provided high quality data and the data has been used towards developing a framework for a standard form of joint venture agreement for construction works